2002
DOI: 10.1046/j.1462-2920.2002.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa displays an epidemic population structure

Abstract: SummaryBacteria can have population structures ranging from the fully sexual to the highly clonal. Despite numerous studies, the population structure of Pseudomonas aeruginosa is still somewhat contentious. We used a polyphasic approach in order to shed new light on this issue. A data set consisting of three outer membrane (lipo)protein gene sequences ( oprI , oprL and oprD ), a DNA-based fingerprint (amplified fragment length polymorphism), serotype and pyoverdine type of 73 P. aeruginosa clinical and environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
122
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 51 publications
11
122
0
4
Order By: Relevance
“…In fact, some of these environmental isolates were members of clones or clonal complexes that possessed isolates from cases of invasive disease. This corroborates assumptions based on previous studies which found no correlations between habitat and particular clones (17,20).…”
Section: Discussionsupporting
confidence: 93%
“…In fact, some of these environmental isolates were members of clones or clonal complexes that possessed isolates from cases of invasive disease. This corroborates assumptions based on previous studies which found no correlations between habitat and particular clones (17,20).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have suggested that there is no correlation between P. aeruginosa clones and diseases or environmental habitats (Foght et al, 1996;Kiewitz & Tummler, 2000;Pirnay et al, 2002;Romling et al, 1994). The use of one or a few strains to represent one disease or environmental habitat may have limited the conclusions of these studies.…”
Section: Discussionmentioning
confidence: 97%
“…Most of these studies have included few or no CF isolates (Denamur et al, 1993;Kiewitz & Tummler, 2000;Lomholt et al, 2001;Pirnay et al, 2002;Ruimy et al, 2001) or have specifically explored the genome of P. aeruginosa isolates from CF patients, especially for epidemiological purposes (Boukadida et al, 1993;Hoogkamp-Korstanje et al, 1995). Fewer studies have demonstrated a link between isolates from CF patients and isolates from environmental habitats (Romling et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Pyocin production was tested on selective Cetrimide Agar aeruginosa strains isolated from faeces (10,11,12,13,14), NCTC 6749 (15) and wound (16,17,18 Results of antibiotic resistance and genotyping showed poor correlation. Resistance patterns from bacterial isolates which had identical genotypes differed in up to 9 antibiotics.…”
Section: Phenotypic Studymentioning
confidence: 99%